Increasing Students’ Communication Skills Using Stimulant Question Model - Eklesias Donesi Andresta; Marmi Sudarmi; Alvama Pattiserlihun (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2018)
The purpose of this study is to make Lesson Plan using stimulant questions that emphasize the communication skills. This research uses CAR method of teacher type as researcher. Respondents from this study were 27 8th grade students of SMP in Salatiga. This research used 5 Lesson Plans with 5 materials. The results indicated that by giving stimulant questions, observers said that 89.22% students were more focused on learning indicated by active students who answered stimulant questions, supported by the results of the questionnaire where 89.34% students said that stimulant questions were in an order, logical, easy to understand, and can help them in solving various problems and the stimulant questions can improve their understanding of physics learning. In addition, the evaluation test results also indicated that 87.18% students understood the material. Therefore, stimulant questions can make students to be focused more and can make them understand the learning materials better.